Efficacy & Safety of Oral Ivermectin and Topical Permethrin in the Treatment of Scabies (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Scabies is one of the most common skin diseases in our country. It is caused by the mite Sarcoptes scabiei var hominis, which is an ecto-parasite infesting the epidermis. Scabies is highly contagious. Prevalence is high in congested or densely populated areas. Individuals with close contact with an affected person should be treated with scabicidal which is available in both oral and topical formulations. The only oral but highly effective scabicidal known to date is Ivermectin. Amongst topical preparations, Permethrin 5 % cream is the treatment of choice.Objective: To evaluate the efficacy & safety of oral Ivermectin compared to topical Permethrin in the treatment of scabies.Methodology: This prospective, non-randomized study was conducted at the out-patient department of Dermatology and Venereology of Shaheed Suhrawardy Medical College & Hospital over a period of 6 months, from August 2016 to January 2017. The study population consisted of one hundred patients having scabies, enrolled according to inclusion criteria. They were divided into two groups. Group A was subjected to oral Ivermectin and the Group B to Permethrin 5% cream. Patient were followed up on day 7, 14 and assessed for the efficacy and safety.Result: The mean scoring with SD in Group A and Group B were 8.26 ± 2.22 and 7.59 ± 2.01respectively at the time of observation. The difference between the mean score of the two group is not significant (p=0.117) The mean scoring with SD in group A and group B were 4.54 ± 2.05 and 1.64 ± 1.84 respectively at 7th days. The difference between the mean score of the two group is significant (p